The politics of judicial co-operation in the EU : Sunday trading, equal treatment, and good faith / Hans-W. Micklitz. - Micklitz, Hans-W (Cambridge University Press, 2005)
The European legal order is largely based on judicial co-operation between the European Court of Justice and the national courts. Three case studies on Sunday trading, on equal treatment of men and women and on good faith in contract law reveal that national courts and national litigants are mainly pursuing national interests by means of European law. The European Court of Justice seeks European solutions by delimiting the scope of the European legal order, by transforming the subjective rights of market citizens into political rights of union citizens, and by developing European remedies to enforce European rights.